2022
DOI: 10.1002/jip.1603
|View full text |Cite
|
Sign up to set email alerts
|

Killing your children to hurt your partner: A South African perspective on the motivations for revenge filicide

Abstract: The aim of the study was to investigate the offence characteristics and motivations for revenge filicides. Revenge filicide is an act where one parent kills their own offspring for retribution to hurt and upset the other parent. The cases of 20 revenge filicide murderers (14 male and six female) were analysed to determine the motivations and offence characteristics of revenge filicide offenders. It is the first South African study to highlight the motivations and associated characteristics in revenge filicides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, there were slight differences. Although spousal revenge filicides figure prominently in the clinical literature (e.g., Moen & Bezuidenhout, 2022), they made up a small portion of the putative motivation in Korean filicides. Similarly, our work also found that mentally ill parents kill their children, but that parents also kill mentally ill offspring.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were slight differences. Although spousal revenge filicides figure prominently in the clinical literature (e.g., Moen & Bezuidenhout, 2022), they made up a small portion of the putative motivation in Korean filicides. Similarly, our work also found that mentally ill parents kill their children, but that parents also kill mentally ill offspring.…”
Section: Discussionmentioning
confidence: 99%